The influence of determining the working length with an apex locator on the amount of apically extruded debris following instrumentation with ProTaper Next and HyFlex CM - Ersan Çiçek; Neslihan Yılmaz; Fatma Furuncuoğlu (Wolters Kluwer Medknow Publications, 2016)
Aim: The amount of apically extruded debris caused by new nickel-titanium rotary systems after determination of the working length (WL) with an apex locator has not been investigated. To compare the amount of apically extruded debris with ProTaper Next (PTN) and HyFlex CM systems after determination of WL with/without an apex locator. Materials and Methods: Forty-eight extracted mandibular incisor teeth divided into four groups were used in this study. In Groups 1 and 2, a 10 K-file was progressed until it was just visible at the major apical foramen and WL was recorded as 1 mm short. In Groups 3 and 4, the WL was determined with the Root ZX (sensitivity of 0.1) using a 10 K-file. During the instrumentation, the PTN was used to X2 in groups 1 and 3, and the HyFlex CM was used to 25/.06 in groups 2 and 4. Distilled water was used as an irrigant. Debris was collected in tubes then stored in an incubator at 68°C for 5 days to evaporate the distilled water. The Eppendorf tubes, including the extruded debris, were weighed to obtain final weights. The amount of extruded debris was calculated by subtracting the weight of the empty tube from the weight of the dry tube. Data were analyzed by Kruskal-Wallis and Mann-Whitney U-test. Results: Less apically extruded debris was obtained in Group 3, with a significant difference compared to Group 1 and Group 2 (P < 0.05). Conclusions: The usage of apex locator to determine the WL decreased the amount of apically extruded debris. In addition, PTN caused less apical debris extrusion after determination WL with/without apex locator.